Circle Up Self-Regulatory Framework: Integrating social, emotional, and academic learning - Gropen, Jess; Bevan, Katie; Wilmot, Bill (Social and Emotional Learning: Research, Practice, and Policy, 2025)
While there is growing recognition that social-emotional learning (SEL) programs integrated with academic learning hold promise for increasing student engagement and academic achievement, there is a need for approaches to integrated SEL that provide an explicit account of how they enhance academic achievement and that can be applied to any subject matter (i.e., that are discipline-agnostic). This Perspectives article presents the Circle Up Self-Regulatory Framework (CU Framework). Drawing on research on motivation, emotion, and self-regulation, the CU Framework addresses the thoughts, feelings, and actions that arise during learning activities as students grapple with reaching their learning goals. Specifically, the Framework is based on an elaboration of Zimmerman’s (2000) self-regulatory cycle and is organized around three person-oriented learning patterns: strategic learning (to help students be strategic in reaching their learning goals); meaningful learning (to help students ignite their passion for learning); and resilient learning (to help students see challenges as opportunities for growth). After each learning pattern is presented, the paper discusses how all three patterns work in combination and how they have been used as a set of constraints on co-designing tools, strategies, and routines with education partners. The paper concludes with a summary and discussion of limitations and future directions. Provides an explicit research-based framework for integrated social-emotional learning (SEL) based on a synthesis of research in self-regulation, motivation, emotion, mindset, and engagement; argues for a goal-oriented approach to integrated SEL that addresses the thoughts, feelings, and actions that arise during learning activities as students grapple with reaching their learning goals; responds to the need for integrated SEL approaches that provide an explicit account of how they enhance academic achievement; responds to the need for more discipline-agnostic integrated SEL programs that can be applied generally; supports student learning that is strategic, meaningful, and resilient; increases student engagement and academic achievement.